Bandgap Assessment of Compositional Variation for Uncovering High‐Efficiency Improved Stable All‐Inorganic Lead‐Free Perovskite Solar Cells. Issue 6 (5th February 2023) - Prabu, R. Thandaiah; Malathi, S. R.; Kumar, Atul; Al-Asbahi, Bandar Ali; Laref, Amel
Abstract : Bandgap evolution with composition variation of ABX3 perovskites is explored, where A = MA, FA, Cs, Rb; B = Pb, Sn, Ge; and X = I, Br, Cl. To identify alternative lead‐free and stable perovskite‐absorbing compositions, all possible combinations of compositions are screened under constraints of structural stability and optimal bandgap values. The comparative analysis reveals Cs‐, Rb‐, and Ge‐based perovskite as an alternative to MAPbI3 's toxicity and stability issues. The Cs‐, Rb‐, and Ge‐based perovskites are lead free and structurally stable, with the requisite optical cum electrical properties. The numerical simulation of the proposed Cs1− y Rb y Ge(Br x I1− x )3 ‐based device shows efficiency above the 22% mark. All aspects of the proposed device are identical to MAPbI3, except that the MAPbI3 absorber is replaced with a Cs1− y Rb y Ge(Br x I1− x )3 ‐based absorber. Abstract : The bandgap and stability with composition variation of ABX3 perovskites (where A = Methylammonium, Formamidinium, Cs, Rb; B = Pb, Sn, Ge; X = I, Br, Cl) were assessed for identifying alternative lead‐free and stable perovskite with high efficiency. The comparative analysis reveals Cs‐, Rb‐, and Ge‐based Cs1−Y RbY Ge(Brx I1−x )3 perovskites as lead free, alternatives to MAPbI3 toxicity and stability.